2020
DOI: 10.1002/adma.202003482
|View full text |Cite
|
Sign up to set email alerts
|

Gap States in Methylammonium Lead Halides: The Link to Dimethylsulfoxide?

Abstract: Understanding the origin and distribution of electronic gap states in metal halide perovskite (MHP) thin films is crucial to the further improvement of the efficiency and long‐term stability of MHP‐based optoelectronic devices. In this work, the impact of Lewis‐basic additives introduced in the precursor solution on the density of states in the perovskite bandgap is investigated. Ultraviolet photoemission spectroscopy and contact potential difference measurements are conducted on MHP thin films processed from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 38 publications
1
23
1
Order By: Relevance
“…3b-Cs, because Cs oxides are known low work-function (B1 eV) materials. 39,54 We note that neither lead oxide nor lead bromate are stable in acid environment. MAPbBr 3 and FAPbBr 3 are reactive towards oxides due to the acidity of the A + cation and would transform to PbBr 2 .…”
Section: Eds Xpsmentioning
confidence: 87%
See 1 more Smart Citation
“…3b-Cs, because Cs oxides are known low work-function (B1 eV) materials. 39,54 We note that neither lead oxide nor lead bromate are stable in acid environment. MAPbBr 3 and FAPbBr 3 are reactive towards oxides due to the acidity of the A + cation and would transform to PbBr 2 .…”
Section: Eds Xpsmentioning
confidence: 87%
“…Ref. 39 shows tail states in high-resolution photoemission spectroscopy, if DMSO is used in HaP film preparation. The assumption in this explanation is that solvent molecules are readily removed from the surface by evaporation, but remain trapped in the bulk.…”
Section: Pl Lifetime Imaging (Fluorescence Lifetime Imaging Microscopy Flim)mentioning
confidence: 99%
“…The transition between the two regimes is not abrupt because of a finite density of states of the corresponding bands at which pinning occurs. Additionally, the presence of tail states near the band edges 32 leads to a more gradual transition. Another observation is that the apparent F sub at which the transition occurs seemingly depends on the MHP film thickness.…”
Section: Energy Level Alignment At Electrode Contactsmentioning
confidence: 99%
“…[ 13 ] One important issue, which is at the center of this work, is the strong variation of the Fermi level ( E F ) position in the energy gap of MHPs, with nominally undoped MHPs reported to exhibit behavior ranging from n‐type to p‐type. [ 14–20 ] For example, Schulz et al. showed that E F in methylammonium lead triiodide (MAPbI 3 ) can be shifted by as much as 0.7 eV solely by varying the substrate from TiO 2 to NiO x .…”
Section: Introductionmentioning
confidence: 99%